In Situ Formation of a MoS2‐Based Inorganic–Organic Nanocomposite by Directed Thermal Decomposition. Issue 24 (29th April 2015) - Djamil, John; Segler, Stefan A. W.; Bensch, Wolfgang; Schürmann, Ulrich; Deng, Mao; Kienle, Lorenz; Hansen, Sven; Beweries, Torsten; von Wüllen, Leo; Rosenfeldt, Sabine; Förster, Stephan; Reinsch, Helge
Abstract Nanocomposites based on molybdenum disulfide (MoS2) and different carbon modifications are intensively investigated in several areas of applications due to their intriguing optical and electrical properties. Addition of a third element may enhance the functionality and application areas of such nanocomposites. Herein, we present a facile synthetic approach based on directed thermal decomposition of (Ph4P)2MoS4 generating MoS2 nanocomposites containing carbon and phosphorous. Decomposition at 250 °C yields a composite material with significantly enlarged MoS2 interlayer distances caused by in situ formation of Ph3PS bonded to the MoS2 slabs through MoS bonds and (Ph4P)2S molecules in the van der Waals gap, as was evidenced by 31P solid‐state NMR spectroscopy. Visible‐light‐driven hydrogen generation demonstrates a high catalytic performance of the materials.